Does recent contact with a health care provider make a difference in Malaria knowledge? - Yamamoto, Shelby; Souares-Coutant, Aurélia; Sié, A.; Sauerborn, Rainer (The journal of tropical pediatrics, 2010)
Knowledge and practices with respect to malaria are aspects that need to be considered as part of effective malaria programs. We assessed and compared malaria practices and knowledge among those who had recently visited a health care provider and those who had not. A matched, population-based case-control study was conducted among 338 women between 15 and 45 years of age and caretakers of children ≤9 years of age in Nouna, Burkina Faso. Little difference was found in the reported responses between the cases and controls, which indicates that recent visits to health care providers may not have an effect on malaria risk or knowledge. Differences were noted in malaria practices, which could suggest that health care providers are consulted only after home treatments fail. Therefore, programs and policies targeted to health care providers aimed at improving the dissemination of information may be of some benefit.
Gesehen am 22.05.2024